Low volume–high intensity interval exercise elicits antioxidant and anti-inflammatory effects in humans. Issue 1 (2nd January 2016) - Wadley, Alex J.; Chen, Yu-Wen; Lip, Gregory Y.H.; Fisher, James P.; Aldred, Sarah
Abstract: The purpose of the present study was to compare acute changes in oxidative stress and inflammation in response to steady state and low volume, high intensity interval exercise (LV-HIIE). Untrained healthy males ( n  = 10, mean ±  s : age 22 ± 3 years; VO2MAX 42.7 ± 5.0 ml · kg −1  · min −1 ) undertook three exercise bouts: a bout of LV-HIIE (10 × 1 min 90% VO2MAX intervals) and two energy-matched steady-state cycling bouts at a moderate (60% VO2MAX ; 27 min, MOD) and high (80% VO2MAX ; 20 min, HIGH) intensity on separate days. Markers of oxidative stress, inflammation and physiological stress were assessed before, at the end of exercise and 30 min post-exercise (post+30). At the end of all exercise bouts, significant changes in lipid hydroperoxides (LOOH) and protein carbonyls (PCs) (LOOH (nM): MOD +0.36; HIGH +3.09; LV-HIIE +5.51 and PC (nmol · mg −1 protein): MOD −0.24; HIGH −0.11; LV-HIIE −0.37) were observed. Total antioxidant capacity (TAC) increased post+30, relative to the end of all exercise bouts (TAC (µM): MOD +189; HIGH +135; LV-HIIE +102). Interleukin (IL)-6 and IL-10 increased post+30 in HIGH and LV-HIIE only ( P  < 0.05). HIGH caused the greatest lymphocytosis, adrenaline and cardiovascular response ( P  < 0.05). At a reduced energy cost and physiological stress, LV-HIIE elicited similar cytokine and oxidative stress responses to HIGH.